Taxation of Crypto Assets in Lithuania and abroad: evaluations, proposals for improvement - Idkinaitė, Sandra; Grumulaitis, Artūras (Vilnius University Open Series, 2023)
The article analyses national and foreign approaches to the legal regulation of ICO, STO and cryptocurrencies from a comparative perspective, examines the models of taxation of crypto assets in Lithuania and Japan, and pays special attention to the legal regulation in Germany as an EU country. It concludes that the tax and legal regulation of cryptocurrencies in Lithuania and Germany is similar, as both countries follow the principle of neutrality – they do not prohibit, but they do not regulate by law. The paper also makes recommendations for recognising cryptocurrencies as legal tender by including regulation of crypto assets in national tax laws, defining types of crypto assets, uniform concepts, and taxation principles. According to the authors, such a solution would provide more legal certainty for natural and legal persons and would help to manage the risks associated with crypto assets.
Keywords: cryptocurrency; crypto assets; taxes; blockchain; ICO